Dampak Kebijakan Larangan Ekspor Biji Nikel Indonesia Terhadap Hubungan Politik Indonesia – Uni Eropa - Sari, Loren Ardana; Sugito, Sugito (Universitas Islam Malang, 2022)
Indonesia officially issued the nickel ore export prohibition policy, which came into impact in January 2020. This policy caused a negative response from the European Union because they felt it violated the principles of free trade. Therefore, this research aimed to examine the impact of Indonesia’s policy of nickel ore export prohibition on its political relations with the European Union. The research used a library research method with data sources from journal articles, books, and other official documents. The research results indicated that the policy of Indonesia’s nickel ore export prohibition impacted the CEPA agreement that Indonesia and the European Union established, which caused the two countries to restructure their negotiation positions. This policy of banning nickel ore exports by Indonesia only affects some political relations. Even so, these implications would not damage the long-standing relationship between the two parties.